Analisis Peran Pembina Ekstrakurikuler Pramuka dalam Menerapkan Karakter Disiplin Anggota Pramuka di SMP Negeri 4 Sungai Raya - Heni Kuswati; Syamsuri Syamsuri; Thomy Sastra Atmaja; Imran Imran; Shilmy Purnama (Journal on Education, 2025)
The purpose of the study was to determine the role of scout coaches as mentors in implementing disciplinary character. knowing the role of coaches as role models in implementing disciplinary character, knowing scout coaches as motivators in implementing disciplinary character, and knowing the strategies used by scout coaches in implementing the disciplinary character of Scout Members at SMP Negeri 4 Sungai Raya. The research method used descriptive method with qualitative research form. The sources of research data are Scoutmaster, Deputy Student Affairs, and Scout Members. Data collection techniques are observation, interview and documentation. Data analysis techniques use data reduction analysis, data presentation, and conclusion drawing. The results of this study are in the form of the role of the Scoutmaster at SMP Negeri 4 Sungai Raya as a mentor, namely providing direction and guidance to students to be disciplined in participating in mandatory scout activities. The Scoutmaster shows an exemplary attitude consistently during extracurricular activities by being present on time and completing tasks properly. As a motivator, the Scoutmaster's role in implementing disciplinary character is by providing motivation and support to scout members through mandatory activities and routine activities. Scoutmasters use strategies in an effort to implement disciplinary character through mandatory activities and routine activities by providing guidance during activities, motivation, role modeling and providing responsibility.